Weaponized Licensure: Asian Migrant Sex Workers’ Struggle Against Discriminatory Licensing in Newmarket, Ontario - Lam, Elene; Wong, Vincent; Chu, Sandra Ka Hon; Chan, Tsz Ching; De Lisio, Amanda (Journal of Critical Race Inquiry, 2024)
This article delves into the recent efforts of Asian migrant massage and sex workers in the Town of Newmarket, Ontario, and their struggle against a recently amended Personal Wellness Establishments (PWE) By-law. It starts with a historical overview of municipal licensing schemes and legislated migration controls in Canada, used to justify increased surveillance, control movement, and deny Asian women entry into Canada, before illustrating the enduring impacts on Asian migrant workers today. It concludes by emphasizing that migrant sex workers, often depicted as voiceless and nonconsenting victims, take leadership and have agency in defining their own struggles and authoring possibilities to resist.